The First Mirror inside the Contrapunctus 6 of the Art of Fugue by Johann Sebastian Bach (BWV 1080, 6) - Alevizos, Konstantinos (Revue musicale OICRM, 2020)
Johann Sebastian Bach had already elaborated the tool of double inversion, inside the Contrapunctus “in stylo francese” of the Art of Fugue. However, the counterpoint tool of double inversion is typical for the two later pairs of fugues BWV 1080, 12-13 a, b. After an examination of the global asset of the Contrapunctus 6, a particular attention is shown to the technique of inversion (mirror) in relation to fugues 12 and 13. Consequently a brief, but methodical, analysis succeeds to demonstrate the existence of totally symmetrical thematic phases inside Contrapunctus 6. The existence of double inversion inside an earlier Contrapunctus can indicate the level of premeditated elaboration in the whole work. Additionally, it could also suppose a parallel or contiguous time of the compositional process among the BWV 1080, 6, 12 and 13, which could re-impose a new examination of the correct order of the Contrapuncti.